Systematic Literature Review: The Implementation of Meaningful Learning in Elementary School Mathematics Education - Anggraini, Tika; Sukiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the implementation of meaningful learning in elementary school mathematics education through a Systematic Literature Review (SLR) approach. Meaningful learning emphasizes the connection between new knowledge and students’ prior knowledge, enabling deeper understanding and long-term retention. The study analyzed 25 selected articles obtained from databases such as Google Scholar, ERIC, and ScienceDirect, published between 2010 and 2024. The selection process followed the PRISMA framework, including identification, screening, eligibility, and inclusion stages. The findings indicate that meaningful learning has a positive impact on students’ conceptual understanding, problem-solving skills, and learning motivation. Various instructional strategies, including contextual learning, problem-based learning, and the use of concrete representations, were found to support the successful implementation of meaningful learning. Additionally, approaches such as Realistic Mathematics Education (RME) were identified as effective in promoting meaningful learning experiences. However, several challenges were identified, including limited teacher understanding, time constraints, and diverse student characteristics. The study also identified research gaps, particularly in the areas of long-term learning outcomes, integration of technology, and the development of students’ mental models. This study concludes that meaningful learning is an effective and relevant approach for improving mathematics education in elementary schools. The results are expected to contribute to the development of teaching practices and future research in the field of mathematics education.